New Cloud Economy For Resolving A Problem Cloud Computing Adoption - Elmahouti, M.; Achandair, O.; Khoulji, S.; Kerkeb, M.L. (Transactions on Engineering and Computing Sciences, 2017)
Cloud computing , IT still called to order, it is a model that allows access to information resources on demand, we can consider it as a unique Technology to satisfy needs and respond to customer demands by guaranteeing an efficient quality of serviceIT management. This paper gives an analysis of cloud computing along its components, also the internal and external institutional factors that influence the adoption of cloud computing in the majority of enterprises. It aims to be innovative by answering these questions of allocation and availability of network services in an intra-datacenter environment by implementing solutions based on new technologies that is OpenStack[1]. The research problem addressed in this paper is the proposal of a new architecture and optimized algorithms of continuity and availability of the service. These will help identify the deployment of existing vulnerabilities. On the other hand, offer a very high level of availability, security and quality of service.